Pembuatan Sabun Cuci Piring Cair Ramah Lingkungan BeEkstrak Kulit Jeruk Nipis (Citrus Aurantiifolia) - Al-Akram, T.M. Rodhie (Jurnal Riset, Inovasi, Teknologi & Terapan, 2024)
ish washing soap is a cleaner made by a chemical reaction between potassium or sodium and fatty acids from vegetable oils or animalfats. Making liquid dishwashing soap from lime peel extract has been carried out using the extraction method. This research aims todetermine the effect of lime peel extract and Methyl Ester Sulfonate (MES) on the characteristics of the liquid dishwashing soap produced,including several tests, namely pH, density, viscosity, bacteria based on SNI 06-2075-1996. Soap making is done by varying the volume oflime peel extract 3, 6, 9, 12, 15 ml and the MES mass 5, 10, 15, 20, 25, 30 grams, as well as adding other ingredients such as NaCl 8 grams,distilled water 300ml, aromatics 2 ml, dye 1 gram. The research results showed that a lime peel extract volume of 6 ml and a MES massof 15 grams produced the best soap with a pH of 6.04, density of 1.099 gr/ml, viscosity of 19.8 cP, bacteria 4 colonies/gr.